A brave new framework for glioma drug development - Hotchkiss, Kelly M.; Karschnia, Philipp; Schreck, Karisa C.; Geurts, Marjolein; Cloughesy, Timothy F.; Huse, Jason; Duke, Elizabeth S.; Lathia, Justin; Ashley, David M.; Nduom, Edjah K.; Long, Georgina; Singh, Kirit; et al. (Lancet Oncology, 2024)
Patients with brain tumours are motivated to participate in clinical trials involving repeat tissue sampling. Normalising the use of neoadjuvant and staged surgical trials necessitates collaboration among patients, regulatory agencies, and researchers. Initial and repetitive tissue sampling plays a crucial role in enhancing our understanding of resistance mechanisms and vulnerabilities in brain tumour therapy. Standardising biopsy techniques and ensuring technical uniformity across institutions are vital for effective interinstitutional collaboration. Although liquid biopsy technologies hold promise, they are not yet ready to replace tissue analysis. Clear communication about the risks and benefits of biopsies is essential, particularly regarding potential postoperative deficits. Changes in mindset and neurosurgical culture are imperative to achieve much needed breakthroughs in the development of new, effective therapies for brain tumours.
CRIS-Team Scopus Importer:2024-10-11

Multidisciplinary management strategies for recurrent brain metastasis after prior radiotherapy: An overview - Kotecha, Rupesh; La Rosa, Alonso; Brown, Paul D.; Vogelbaum, Michael A.; Navarria, Pierina; Bodensohn, Raphael; Niyazi, Maximilian; Karschnia, Philipp; Minniti, Giuseppe (Neuro-Oncology, 2025)
As cancer patients with intracranial metastatic disease experience increasingly prolonged survival, the diagnosis and management of recurrent brain metastasis pose significant challenges in clinical practice. Prior to deciding upon a management strategy, it is necessary to ascertain whether patients have recurrent/progressive disease vs adverse radiation effect, classify the recurrence as local or distant in the brain, evaluate the extent of intracranial disease (size, number and location of lesions, and brain metastasis velocity), the status of extracranial disease, and enumerate the interval from the last intracranially directed intervention to disease recurrence. A spectrum of salvage local treatment options includes surgery (resection and laser interstitial thermal therapy [LITT]) with or without adjuvant radiotherapy in the forms of external beam radiotherapy, intraoperative radiotherapy, or brachytherapy. Nonoperative salvage local treatments also range from single fraction and fractionated stereotactic radiosurgery (SRS/FSRS) to whole brain radiation therapy (WBRT). Optimal integration of systemic therapies, preferably with central nervous system (CNS) activity, may also require reinterrogation of brain metastasis tissue to identify actionable molecular alterations specific to intracranial progressive disease. Ultimately, the selection of the appropriate management approach necessitates a sophisticated understanding of patient, tumor, and prior treatment-related factors and is often multimodal; hence, interdisciplinary evaluation for such patients is indispensable.
CRIS-Team Scopus Importer:2025-04-04
Keywords: brain metastases; progression; radiosurgery; radiotherapy; recurrence

The Infiltrative Margins in Glioblastoma: Important Is What Has Been Left behind - Karschnia, Philipp; Tonn, Joerg Christian; Cahill, Daniel P. (Clinical Cancer Research, 2024)
Supramaximal resection beyond the contrast-enhancing tumor borders represents an emerging surgical strategy for patients with newly diagnosed glioblastoma. A recent study provides evidence detailing the interactive effects of more aggressive surgery on other clinical predictors of outcome, supporting guidance for surgical decision-making and informing clinical trialists about the need to stratify for extent of resection.
CRIS-Team Scopus Importer:2024-11-15